2016
DOI: 10.1371/journal.pone.0157422
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Mechanism and Global Quantification of Breast Cancer

Abstract: Initiation and progression of cancer depend on many factors. Those on the genetic level are often considered crucial. To gain insight into the physical mechanisms of breast cancer, we construct a gene regulatory network (GRN) which reflects both genetic and environmental aspects of breast cancer. The construction of the GRN is based on available experimental data. Three basins of attraction, representing the normal, premalignant and cancer states respectively, were found on the phenotypic landscape. The progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
(37 reference statements)
5
25
0
Order By: Relevance
“…Thus, it is suggested that the results herein might correlate with existing reports [ 36 , 41 ] where the described presence of mutations could correspond to the lower levels of TP53 in neoplastic tissues found in our study. Moreover, TP53 is known to be a tumor suppressor gene [ 42 ] and, therefore, its lower expression in neoplastic tissues might lead to uncontrolled cellular growth, a fact which corroborates the findings herein. Further studies at mRNA level are worth carrying out to deepen existing knowledge concerning the role of this gene in CMT.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it is suggested that the results herein might correlate with existing reports [ 36 , 41 ] where the described presence of mutations could correspond to the lower levels of TP53 in neoplastic tissues found in our study. Moreover, TP53 is known to be a tumor suppressor gene [ 42 ] and, therefore, its lower expression in neoplastic tissues might lead to uncontrolled cellular growth, a fact which corroborates the findings herein. Further studies at mRNA level are worth carrying out to deepen existing knowledge concerning the role of this gene in CMT.…”
Section: Discussionsupporting
confidence: 88%
“…So this path is dominant for Normal to Cancer state transition. Therefore, to prevent cancer formation, this is worthy attention and we have demonstrated the importance of Premalignant state for cancer prevention in our previous work [29].…”
Section: Barrier Heights and Flux Of Kinetic Pathsmentioning
confidence: 84%
“…To emphasize the characteristics of CSCs, EMT and cancer, a core gene regulatory network motif covers specific genes and micro-RNAs of the three aspects. As shown in Fig.1, MDM2 is an oncogene of cancer, P53 is a well known tumor suppressor gene [29]. ZEB is an EMT activator gene which suppresses the stemness-inhibition of micro-RNA (mir-200) [30].…”
Section: Model Constructionmentioning
confidence: 99%
“…But for Lv- cxcl12 -MSCs, overproduction of CXCL12 would assist metastasis of CXCR4 + cancer cells, including colorectal cancer cells 39 . Nevertheless, we believe that the potential risks of Lv- cxcl12 -MSCs can be theoretically quantified by identifying the critical elements such as genes or gene regulations responsible for that from the underlying gene regulatory networks by characterizing the Waddington landscapes and biological paths for normal and cancer developments as well as the cancer stem cells under various environmental conditions including epigenetics 40 49 . This will be the future work for us to explore.…”
Section: Discussionmentioning
confidence: 99%